2016
DOI: 10.1371/journal.pone.0167638
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Selective Growth-Inhibitory Effect of 8-Hydroxyquinoline on Clostridium perfringens versus Bifidobacteria in a Medium Containing Chicken Ileal Digesta

Abstract: Clostridium perfringens-induced necrotic enteritis is generally controlled by antibiotics. However, because of increasing antibiotic resistance, other antibacterial agents are required, preferably ones that do not affect the beneficial intestinal microbiota of the host. This study evaluated the in vitro selective growth-inhibitory effect of 8-hydroxyquinoline (8HQ) on C. perfringens vs. bifidobacteria in a medium containing chicken ileal digesta. Prior to the experiments, the minimum inhibitory concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The selective antibacterial activity of 8-hydroxyquinoline against diarrheagenic pathogens seems to be enhanced with chlorine halogenation or by the presence of a nitro group and decreased with iodine halogenation and the presence of a sulfo group, as respectively observed for chloroxine, nitroxoline, and ferron in our study. The in vitro selective anticlostridial effect of 8-hydroxyquinoline with increased resistance of bifidobacteria was previously described in studies of Novakova et al [ 10 , 27 , 28 ], Skrivanova et al [ 29 ], and Kim et al [ 30 ]. However, data on its in vitro growth-inhibitory effects against a broader selection of diarrheagenic bacteria are limited.…”
Section: Discussionmentioning
confidence: 98%
“…The selective antibacterial activity of 8-hydroxyquinoline against diarrheagenic pathogens seems to be enhanced with chlorine halogenation or by the presence of a nitro group and decreased with iodine halogenation and the presence of a sulfo group, as respectively observed for chloroxine, nitroxoline, and ferron in our study. The in vitro selective anticlostridial effect of 8-hydroxyquinoline with increased resistance of bifidobacteria was previously described in studies of Novakova et al [ 10 , 27 , 28 ], Skrivanova et al [ 29 ], and Kim et al [ 30 ]. However, data on its in vitro growth-inhibitory effects against a broader selection of diarrheagenic bacteria are limited.…”
Section: Discussionmentioning
confidence: 98%
“…8-Hydroxyquinoline (oxine, 8-quinolinol, 8HQ) is an alkaloid with a rather simple chemical structure and occurs in plants of families Asteraceae [1] and Euphorbiaceae [2]. Previous studies revealed a very large spectrum of various biological activities, such as phytotoxic [1,3], antibacterial [4,5], antifungal [6], and insecticidal [2] activities for 8HQ and structurally related compounds. In recent decades, however, its potential as a cure for some neurodegenerative diseases such as Alzheimer’s and Parkinson’s diseases raised attention [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It seems an intricate network of signaling pathways reported to be involved in NO production. 35 - 37 Irrespective of an inevitable role of PI3K/Akt/mTOR axis iNOS expression, several studies showed HCQ blunted the generation of NO by eliminating 20S proteasomal activation and reduction of interferon-β in macrophages and chondrocytes. 38 In accordance with our data, Gómez-Guzmán et al acclaimed that chronic using of HCQ could protect kidney and improve endothelial cell dysfunction by decreasing ROS level in autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%